Social Partnership in Russia: Prerequisites, Problems and Trends - FROLOVA, Elena V.; MEDVEDEVA, Natalia V.; KABANOVA, Elena E.; KURBAKOVA, Svetlana N.; VINICHENKO, Mikhail V. (Journal of Advanced Research in Law and Economics; Vol 7 No 2 (2016): JARLE, Volume VII, Issue 2(16), Spring 2016, 2016)
The article deals with social partnership as a system of relationships in which the three sectors, the government, business and society, act as the subjects of partnerships while a set of social problems serves as the object. To date, the social and economic premises for the development of social partnership between business and government in the Russian Federation, particularly at the municipal level, have not been fully explored, since the social welfare of both the regions and the country as a whole depends on sustainable social and economic development of municipalities. The scientific and practical significance lies in analyzing and identifying key issues that restrict the development of social partnership at the municipal level in the current conditions. On the basis of the analysis, the authors note the prevailing objective contradiction between the municipalities’ need for private investment funds and lack of them. This problem suggests that in today's market conditions more flexible mechanisms for attracting business to solve local issues have to be used. The paper summarizes the current practices for implementing public-private partnership projects and identifies priority ones. The research concludes that more active implementation of the partnership approach is needed to address the problems of local governments. This will help create new opportunities for social development through capabilities of each sector and new ways of their application.